Comparing sea ice areas identified within quad-polarimetry high-resolution SAR satellite scenes with the same areas in dual-polarimetry medium resolution SAR scenes - Hvidsten, Magnus (UiT The Arctic University of Norway, 2018)
This thesis compares polarimetric features from quad-polarimetric (quad-pol) SAR (synthetic aperture radar) data and emulated dual-polarimetric (dual-pol) SAR data to investigate the information captured over sea ice areas located in the Barents Sea. The polarimetric features of entropy (H) and mean alpha, and the H/mean alpha-plot is compared, as well as the cross-polarizarion ratio and the damping ratio. It is shown that the interpretation of H, mean alpha, and the H/mean alpha-plot from emulated dual-polarimetric HH/HV data are not consistent with conventional interpretation of H, mean alpha, and the H/mean alpha-plot. The cross-polarization ratio and the damping ratio yielded promising results, and it was shown that for the data utilized in the thesis constituents of a given size can be separated from its surroundings in the emulated dual-polarimetric HH/HV data.